A cost-effectiveness analysis of the combination of serplulimab with chemotherapy for advanced esophageal squamous cell carcinoma: insights from the ASTRUM-007 trial - Jiahui Li; Chaoqun Xu; Suyun Yuan (Cost Effectiveness and Resource Allocation, 2024)
Abstract Background Combined serplulimab and chemotherapy demonstrated improved clinical survival outcomes in patients with advanced esophageal squamous cell carcinoma (ESCC) and PD-L1 combined positive scores (CPS) ≥ 1. The present study aimed to evaluate the economic viability of integrating serplulimab in combination with chemotherapy as a potential therapeutic approach for treating ESCC in China. Methods A Markov model was constructed to evaluate the economic and health-related implications of combining serplulimab with chemotherapy. With the incremental cost-effectiveness ratio (ICER), costs and results in terms of health were estimated. For assessing parameter uncertainty, one-way and probabilistic sensitivity studies were carried out. Results The combination of serplulimab and chemotherapy yielded incremental costs and QALYs of $3,163 and 0.14, $2,418 and 0.10, and $3,849 and 0.15, respectively, for the overall population as well as patients with PD-L1 CPS1-10 and PD-L1 CPS ≥ 10. This corresponds to ICER values per QALY of $23,657, $23,982, and $25,134. At the prespecified WTP limit, the probabilities of serplulimab with chemotherapy being the preferred intervention option were 74.4%, 61.3%, and 78.1% for the entire patient population, those with PD-L1 1 ≤ CPS < 10, and those with PD-L1 CPS ≥ 10, respectively. The stability of the presented model was confirmed through sensitivity studies. Conclusions In conclusion, the combination of Serplulimab and chemotherapy showed excellent cost-effectiveness compared to chemotherapy alone in treating PD-L1-positive patients with ESCC in China.